Księgozbiór panien norbertanek w Imbramowicach - Bielak, Włodzimierz (Archiwa, Biblioteki i Muzea Kościelne, 2011)
The article presents the convent book collection of the Norbertine Sisters in Ibramowice. Its beginnings date back to the first half of the 18th century. The convent was rebuilt after the fi re in 1710. Then its greatest benefactor, the Rev. Dominik Lochman, made an effort to found a library to which he himself gave a lot of books. The library established by the Rev. Lochman grew bigger throughout the following years. The books mainly came from donors, but some of them were brought by sisters who entered the convent, including those nuns who were resettled from dissolved convents, for example from Busko. The present–day book collection is divided into five categories: manuscripts, antique books, nineteenth-century books, modern books and magazines. The size of the book collection is not exactly known. So far it has been possible to confirm the existence of about 30 music manuscripts, which were written from the 18th to the 19th century, over 800 antique books and over 300 titles of magazines. The most valuable books are the thirteenth-century antiphonaries of Płock, the fifteenthcentury gradual and a few extremely rare antique books.